Synthesis of Superabsorbent Polymer via Inverse Suspension Method: Effect of Carbon Filler - Munirah Ezzah, Tuan Zakaria; Saidatul Shima, Jamari; Yeong, Yi Ling; Suriati, Ghazali (IOP Publishing, 2017)
This paper studies on the effect of the addition of carbon filler towards the performance of superabsorbent polymer composite (SAPc). In this work, the SAPc was synthesized using inverse suspension polymerization method. The process involved two different solutions; dispersed phase which contains partially neutralized acrylic acid, acrylamide, APS and NN-Methylenebisacrylamide, and continuous phase which contains cyclohexane, span-80 and carbon filler (at different weight percent). The optimum SAPs and filler ratio was measured in terms of water retention in soil and characterized by Mastersizer, FTIR and SEM. Biodegradability of the polymer was determined by soil burial test and SAPc with 0.02% carbon has highest biodegradability rate. SAPc with 0.04wt% carbon showed the optimal water retention percentage among all the samples. The synthesized SAPc producing spherical shapes with parallel alignment due to the addition of carbon fiber. It can be concluded that the addition of carbon fiber able to enhance the performance of the SAP composite (SAPc).